Processing of dense bioinspired ceramics with complex microstructures and weak interfaces - Behera, Rohit Pratyush (Nanyang Technological University, 2023)
Biological ceramic composites are widespread in nature and exhibit mutually exclusive properties like strength and toughness, despite having high mineral content. In contrast, most synthetic materials are either stiff and strong such as ceramics, or tough and less stiff such as polymers or metals, but seldom feature both properties. A composite could offer a solution to achieve mutually exclusive properties from its constituents; however, the extent of improvement is limited. Nevertheless, biological ceramic composites exhibit superior mutually exclusive properties with the help of the hierarchical arrangement of constituents in their structure. This hierarchical arrangement also helps to achieve multiple functions such as lightweight, mobility, impact protection, body support, etc. Additionally, these hierarchical arrangements often have a complex design of structural motifs like the layered motif in the brick-and-mortar organization of the abalone shell, the helicoidal or Bouligand motif of fibers in the periodic region of the dactyl club, and the gradient motif in the impact surface and region of the dactyl club, etc., each structural motif serving specific functionality. Furthermore, extrinsic toughening mechanisms, such as crack deflection, multiple cracking, etc., are generated due to the hierarchical structural arrangement of reinforcing materials, which help dissipate energy. Although such properties of biological composites are fascinating, the fabrication technologies to achieve high mineral content while attaining a high degree of reinforcement orientation along preferred directions in synthetic composites are still limited. To address these issues, this thesis explores a bottom-up hierarchical assembly technique for fast fabrication that controls the directional orientation of ceramic reinforcement. With this technique, this work focuses on fabricating hierarchical composites with structural motifs and weak interfaces to achieve high strength and toughness using rational design. For fabrication, micron-sized platelet-shaped aluminium oxide (alumina) platelets are used as reinforcement. Iron oxide nanoparticles (Fe3O4 np) are adsorbed on the surface of the microplatelets to make them magnetically responsive. Then, an aqueous colloidal suspension or a slurry of the magnetized microplatelets is prepared by adding alumina nanoparticles. This enables the magnetized microplatelets to be oriented in any intended direction using a magnetic field following a process called magnetic assisted slip casting (MASC). In the process, while the slurry consolidates to fix the orientation of the microplatelets in place, the alumina nanoparticles are trapped in between microplatelets. The formed green body is then sintered, allowing the alumina nanoparticles to be consumed into the alumina microplatelets leading to anisotropic grain growth, a process called templated grain growth (TGG). Thus, the final ceramic obtained is dense and textured. Using MASC and TGG, complex bioinspired hierarchical structures were fabricated: nacre-inspired, Bouligand-inspired, and a multi-layered structure named impact region-inspired. To enable MASC, compositional parameters were optimized and selected for desirable structural properties (orientations and relative density) in each structure. To enable TGG, the sintering was conducted at first using pressureless conventional sintering (CS). The bioinspired structures sintered for 10 h exhibited competitive compressive and flexural properties after polymer infiltration. However, they did not show resistance to crack growth in the fracture toughness tests. It is hypothesized that this is due to the strong interfacial bonding between adjacent alumina grains, which promotes transgranular fracture and results in brittleness. To solve the issue, ultrafast high-temperature sintering (UHS) is explored for the same green bodies. First, one slurry composition was chosen for sintering green bodies of ~ 1 mm thickness and 2-3 mm lateral dimensions. The sintering parameters were tuned, and the highest relative density and texture were obtained at a sintering temperature ~ 1700 °C, a sintering time of 10 s, and a heating rate of 5500 ℃/min. At these sintering conditions, there is limited diffusion of Fe3O4 with enhanced relative density compared to CS. Second, the process was scaled up to sinter bulk bioinspired green bodies of dimensions ~ 3 mm in thickness and 20 × 4 mm in length and width. All three sintered bioinspired ceramic structures retained the appropriate microstructure and texture after UHS with higher relative density than the CS. Interfacial Fe3O4 nanoparticles were also found in these structures, which contribute to weakening the grain interfaces leading to enhanced energy dissipation. Moreover, all the ceramic structures retained local anisotropic mechanical properties at the nano and micro scales according to the local grain orientation and the microstructural arrangement. After polymer infiltration, the compressive and flexural strength was comparable, while the moduli were lower compared to the structures sintered by CS for 10 h. However, the strain at failure was generally higher for structures sintering by UHS. Noticeably, all the bioinspired composite structures processed using UHS exhibited an increasing crack growth resistance. These composites, therefore, displayed mutually exclusive properties, with the nacre-inspired structure exhibiting flexural strength (σ_F) ~ 290 MPa and fracture toughness (K_Jc) of ~ 7 MPa.m0.5, the Bouligand-inspired showing σ_F ~ 155 MPa and K_Jc of ~ 5 MPa.m0.5, the impact region-inspired demonstrating σ_F ~ 215 MPa and K_Jc ~ 10 MPa.m0.5. Comparing the properties of the materials prepared by MASC and UHS with other material systems and commonly used engineering materials indicates that the fabrication process developed in this thesis is efficient, and the mechanical performance achieved could be suitable for structural, transport, and energy absorption applications. Overall, the findings of this thesis contribute to the understanding of sintering processes onto the properties of ceramics and enable the rational design of bioinspired ceramic composites with unusual combinations of properties. Future work could focus on other optimized designs for specific applications and scale-up.